Pro-inflammatory dietary patterns and their association with cardiovascular disease and pancreatic cancer in a hospital population: a cross-sectional study - Jin, Qiangsong; Liu, Yujin; Tong, Qiang; Tang, Biao; Liang, Feng; Zeng, Lingling (Frontiers in Nutrition, 2026)
ObjectiveTo examine whether a concise, clinic-feasible Patient Inflammatory Diet Score (PIDS) relates to prevalent pancreatic cancer and cardiovascular disease (CVD) in a hospital population, and to explore associations with systemic inflammation.MethodsWe conducted a cross-sectional study among 401 adults (≥40 years) attending cardiology, gastroenterology, or oncology services (2018–2022). A 10–12-min questionnaire captured sociodemographics, lifestyle, and habitual intake of pro- and anti-inflammatory food groups to derive the PIDS (quartiles). Pancreatic cancer and CVD were ascertained from de-identified electronic records; high-sensitivity C-reactive protein (hsCRP) indexed systemic inflammation. Robust Poisson models estimated prevalence ratios (PRs) across PIDS quartiles with prespecified adjustments and subgroup/sensitivity analyses.ResultsPancreatic cancer was present in 24 participants (6.0%); CVD in 111 (27.7%). Relative to Q1, fully adjusted PRs for pancreatic cancer were 0.81 (95% CI 0.32–2.06), 0.94 (0.39–2.27), and 1.09 (0.45–2.65) for Q2–Q4 (p-trend = 0.79); the per-SD estimate was 1.03 (0.81–1.31). PIDS showed no material association with prevalent CVD (Q4 vs. Q1, PR 1.08; 0.76–1.54; p-trend = 0.61). Correlation with hsCRP was weak (ρ = 0.09; p = 0.08), and findings were consistent across sex, age, and BMI strata, alternative PIDS categorizations, exclusion of hsCRP > 10 mg·L−1, and restriction to participants without CVD. No synergistic effects were observed for joint PIDS–CVD categories.ConclusionIn this pragmatic clinical setting, a brief, food-based inflammatory diet score did not discriminate cross-sectional differences in pancreatic-cancer prevalence or CVD, nor did it correlate meaningfully with hsCRP. These null findings bound plausible effect sizes and support the need for larger, prospective studies with richer dietary phenotyping and biomarker integration.